Do the definitions of the underactive bladder and detrusor underactivity help in managing patients: International Consultation on Incontinence Research Society (ICI-RS) Think Tank 2017? - TARCAN, TUFAN (WILEY, 2018)
AimsThe Think Tank aimed to discuss the pitfalls and advantages of current definitions in terms of research and management of underactive bladder (UAB). UAB broadly defines a symptom complex of bladder emptying problems and does not indicate a specific pathology. Detrusor underactivity (DU) is a urodynamic diagnosis from pressure-flow studies. The correlation of UAB with DU remains to be precisely determined. MethodsThe presentations and subsequent discussion, leading to research recommendations during the Think Tank of the International Consultation on Incontinence Research Society in Bristol, 2017, are summarized. ResultsTo develop more specific individualized management strategies, the Think Tank panel proposed (i) that, since defining a single type of index patient to represent all UAB will not fulfill all clinical research needs, several index patients should be defined by phenotyping of patients with UAB, including, children, young men and women, elderly male and female patients with co-existing DU and detrusor overactivity, and neurological patients with UAB; (ii) prospective longitudinal studies to assess the natural history of UAB, in the different target populations, based on different UAB phenotypes, should be initiated; (iii) DU should be precisely defined by urodynamic parameters; and (iv) work to develop validated specific questionnaires combined with non-invasive tests for screening, diagnosis and follow up, needs to be continued. ConclusionsThe precise relationship of UAB to DU remains to be defined. Phenotyping patients with UAB/DU, performing prospective trials of natural history, and developing symptom questionnaires and diagnostic investigations will improve our ability to identify and treat UAB/DU.
Keywords: detrusor underactivity; dysfunctional voiding; Fowler's syndrome; terminology; underactive bladder; urodynamics; URINARY-TRACT SYMPTOMS; NATURAL-HISTORY; VOIDING DYSFUNCTION; OVERACTIVE BLADDER; CLINICAL-SIGNIFICANCE; URODYNAMIC FINDINGS; FOWLERS-SYNDROME; YOUNG MEN; WOMEN; CHILDREN